2021
DOI: 10.3389/fpsyt.2021.685910
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Abundance of Haemophilus in the Gut Microbiota and Negative Symptoms of Schizophrenia

Abstract: Increasing evidence indicates an interaction between dysbiosis of the microbiota and the pathogenesis of schizophrenia. However, limited information is available on the specific microbial communities associated with symptoms of schizophrenia. Therefore, this study aimed to investigate gut microbiota dysbiosis and its relationship with psychopathologies in schizophrenia. We recruited 126 participants and divided them into three groups according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 42 publications
1
24
0
2
Order By: Relevance
“… 127 Furthermore, the gut microbiota has been shown to differentiate between acute schizophrenia and remission. 128 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 127 Furthermore, the gut microbiota has been shown to differentiate between acute schizophrenia and remission. 128 …”
Section: Methodsmentioning
confidence: 99%
“…In addition, Lachnospiraceae has been associated with chronic schizophrenia 127. Furthermore, the gut microbiota has been shown to differentiate between acute schizophrenia and remission 128…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the abundance of Haemophilus was positively correlated with negative symptoms, cognition, excitement, and depression, whereas Coprococcus was found to be negatively correlated with negative symptoms. 69 In line with this, Pan et al 76 have reported that compared with acute SCZ, remission SCZ patients had increased abundances of family Clostridiaceae-1 and genus Clostridium sensu-stricto-1 and unclassified family Peptostreptococcaceae . 76 Moreover, there was positive correlation between Succinivibrio abundance and total and general Positive and Negative Symptom Scale (PANSS) scores, while Corynebacterium was negatively correlated with the negative scores of PANSS.…”
Section: Resultsmentioning
confidence: 80%
“… 67 , 68 SCZ patients also showed increased serum and fecal concentrations of SCFAs, which was negatively correlated with cognitive function. Patients with higher circulating SCFAs showed immune activation evidenced by increased CRP, IL-6, soluble IL-2R, and sCD14 in Zhu et al 60 , 69 …”
Section: Resultsmentioning
confidence: 98%